Towards health justice: Implementing structural competency in women’s healthcare education - Daina Charnelle Fougang; Charles Mpofu; Dianne Wepa (International Journal of Africa Nursing Sciences)
Introduction: The World Health Organization advocates for preparing medical students to address health disparities experienced by minority groups. The persistent disparities in women’s health outcomes, particularly among racial and ethnic minorities, highlight critical gaps in current medical education approaches. Despite strong consensus about the significance of structural competence training in medical education, most curricula struggle to develop, teach, and assess it effectively, particularly in addressing women’s health disparities. Objectives: This systematic review aims to: (1) evaluate structural competency’s role in women’s health disparities and (2) develop implementation strategies for women’s healthcare education. Methodology: A systematic literature review using Scopus, Google Scholar, and Web of Science databases (2010–2023) initially identified 905 articles. Following rigorous inclusion criteria focusing on structural competency, women’s health disparities, and medical education, 40 articles were selected for final analysis. Findings: The review presents (1) comprehensive evidence of health disparities in women’s healthcare, particularly affecting racial and ethnic minorities; (2) the critical role of structural competency in addressing systemic barriers and discrimination in healthcare delivery; (3) effective teaching strategies including lecture-based, case-based, team-based, and simulation-based learning approaches; Findings indicate that successful implementation of structural competency requires multi-level interventions across individual, interpersonal, clinic, community, research, and policy domains. Conclusion: This review establishes the importance of integrating structural competency into women’s healthcare education. While implementation challenges exist, the framework developed provides practical guidance to address women’s health disparities through structural competency training.